Cell Wall Polymer Composition and Spatial Distribution in Ripe Banana and Mango Fruit: Implications for Cell Adhesion and Texture Perception - Rongkaumpan, Ganittha; Amsbury, Sam; Andablo-Reyes, Efren; Linford, Holly; Connell, Simon; Knox, J. Paul; Sarkar, Anwesha; Benitez-Alfonso, Yoselin; Orfila, Caroline (Frontiers in Plant Science, 2019)
Banana (Musa acuminata) and mango (Mangifera indica) are two of the most popular fruits eaten worldwide. They both soften during ripening but their textural attributes are markedly different. This study aimed to elucidate the molecular mechanism underpinning textural differences between banana and mango. We used a novel combination of methods at different scales to analyse the surface properties of fruit cells and the potential contribution of cells and cell wall components to oral processing and texture perception. The results indicated that cell separation occurred easily in both organs under mild mechanical stress. Banana cells showed distinctively elongated shapes with distinct distribution of pectin and hemicellulose epitopes at the cell surface. In contrast, mango had relatively spherical cells that ruptured during cell separation. Atomic force microscopy detected soft surfaces indicative of middle lamella remnants on banana cells, while mango cells had cleaner, smoother surfaces, suggesting absence of middle lamellae and more advanced cell wall disassembly. Comparison of solubilized polymers by cell wall glycome analysis showed abundance of mannan and feruylated xylan in separation exudate from banana but not mango, but comparable levels of pectin and arabinogalactan proteins. Bulk rheology experiments showed that both fruits had similar apparent viscosity and hence might be extrapolated to have similar ‘oral thickness’ perception. On the other hand, oral tribology experiments showed significant differences in their frictional behaviour at orally relevant speeds. The instrumental lubrication behavior can be interpreted as ‘smooth’ mouthfeel for mango as compared to ‘astringent’ or ‘dry’ for banana in the later stages of oral processing. The results suggest that cell wall surface properties contribute to lubricating behavior associated with textural perception in the oral phase.